ANALISIS INFRASTRUKTUR TEKNOLOGI INFORMASI PADA WEB E-LEARNING UNIVERSITAS AMIKOM PURWOKERTO MENGGUNAKAN METODE SWOT DAN BALANCED SCORECARD - Afrilia Wanti Puspita Ayu; Annisa Rahma (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study analyzes the information technology infrastructure of the Web E-Learning system at Universitas Amikom Purwokerto using the SWOT and Balanced Scorecard (BSC) methods. Data were collected through interviews with system administrators to evaluate hardware, software, network, data security, and human resources. The SWOT analysis identifies strengths such as stable internal servers, secure backup mechanisms, user-driven feature development, and trained IT staff, while weaknesses include reactive bug handling and irregular system updates. Opportunities arise from institutional digital support and rapid technological growth, whereas threats involve cybersecurity risks and technological shifts. Through the BSC framework, the system demonstrates efficiency, user satisfaction, and strong operational support. The findings highlight that the Web E-Learning infrastructure performs well but requires continuous improvements to remain adaptive to digital advancements.